2017
DOI: 10.1002/jcsm.12180
|View full text |Cite
|
Sign up to set email alerts
|

Psoas muscle area is not representative of total skeletal muscle area in the assessment of sarcopenia in ovarian cancer

Abstract: BackgroundComputed tomography measurements of total skeletal muscle area can detect changes and predict overall survival (OS) in patients with advanced ovarian cancer. This study investigates whether assessment of psoas muscle area reflects total muscle area and can be used to assess sarcopenia in ovarian cancer patients.MethodsOvarian cancer patients (n = 150) treated with induction chemotherapy and interval debulking were enrolled retrospectively in this longitudinal study. Muscle was measured cross sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
146
2
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 163 publications
(157 citation statements)
references
References 31 publications
(66 reference statements)
8
146
2
1
Order By: Relevance
“…Rutten et al . found that while their linear method took very little time to implement (<1 min per scan), there was a poor correlation between the psoas linear area (length × width) and the total cross‐sectional area ( r  = 0.39) among 150 ovarian cancer patients and no associations with psoas linear area and survival 25. By contrast, Jones et al .…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Rutten et al . found that while their linear method took very little time to implement (<1 min per scan), there was a poor correlation between the psoas linear area (length × width) and the total cross‐sectional area ( r  = 0.39) among 150 ovarian cancer patients and no associations with psoas linear area and survival 25. By contrast, Jones et al .…”
Section: Discussionmentioning
confidence: 97%
“…While smaller studies have taken linear measures of the psoas among colorectal26 and ovarian cancer25 patients, ours is the largest study to use the technique developed by Avrutin et al . to take linear measures of multiple muscle groups (the psoas and paraspinal) among colorectal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations